Chloroplast genomes of Arabidopsis halleri ssp. gemmifera and Arabidopsis lyrata ssp. petraea: Structures and comparative analysis - Sajjad Asaf (Nature Portfolio, 2017)
Abstract We investigated the complete chloroplast (cp) genomes of non-model Arabidopsis halleri ssp. gemmifera and Arabidopsis lyrata ssp. petraea using Illumina paired-end sequencing to understand their genetic organization and structure. Detailed bioinformatics analysis revealed genome sizes of both subspecies ranging between 154.4~154.5 kbp, with a large single-copy region (84,197~84,158 bp), a small single-copy region (17,738~17,813 bp) and pair of inverted repeats (IRa/IRb; 26,264~26,259 bp). Both cp genomes encode 130 genes, including 85 protein-coding genes, eight ribosomal RNA genes and 37 transfer RNA genes. Whole cp genome comparison of A. halleri ssp. gemmifera and A. lyrata ssp. petraea, along with ten other Arabidopsis species, showed an overall high degree of sequence similarity, with divergence among some intergenic spacers. The location and distribution of repeat sequences were determined, and sequence divergences of shared genes were calculated among related species. Comparative phylogenetic analysis of the entire genomic data set and 70 shared genes between both cp genomes confirmed the previous phylogeny and generated phylogenetic trees with the same topologies. The sister species of A. halleri ssp. gemmifera is A. umezawana, whereas the closest relative of A. lyrata spp. petraea is A. arenicola.